Phenol adsorption performance by bamboo activated carbon produced using fabricated two-in-one carbonization activation pilot reactor - Mohd Fairus, Mariam Jamilah; Ibrahim, Mohamad Faizal; Zainal, Nahrul Hayawin; Abd-Aziz, Suraini; Phang, Lai-Yee (Elsevier, 2025)
Phenol contamination from industrial effluents poses significant risks to ecosystems and human health. The permissible limit for phenol levels in wastewater sets by the Malaysia Environmental Quality Act of 1974 is 1 mg L⁻¹ (Standard B). Therefore, this study produced bamboo activated carbon (BAC) using a pilot-scale of two-in-one carbonization and activation reactor and tested for phenol removal. BAC was carbonized at 500°C for 2 h, followed by physical activation at 800°C for 2 h. The resulting BAC demonstrated a remarkable surface area of 1018 m² g⁻¹, a high microporosity exceeding 80 %, and a minor presence of mesoporosity with a pore diameter of 2.08 nm. These characteristics greatly enhanced phenol removal, with BAC achieving over 90 % removal within 15 min at 0.4 g dosage, whereas commercial BAC reached only 82.4 % at the same dosage after 60 min. Additionally, BAC remained effective across a wide pH range of 2–10. The adsorption followed pseudo-first-order kinetics (R² = 0.9995, χ² = 0.0049) and multilayer adsorption as per the Freundlich isotherm model (R² = 0.9588, χ² = 0.9119). These results demonstrate the high potential of BAC produced from this reactor for effective phenol removal, with potential applications for other pollutants.